AUDIT MANAJEMEN UNTUK MENGEVALUASI EFEKTIVITAS DAN EFISIENSI REKRUTMEN SUMBER DAYA MANUSIA - Anawati, Lusi; Ngumar, Sutjipto (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Human resources is a potential assets which is owned by the organization and it has important role inachieving the goal. The HRD activities include recruitment, selection, reward and punishment. In order toachieve good HR the company is required to do the evaluation to the selection of employees through the process ofmanagement audit. Management audit is an examination of all aspects of operations of the company in order toprovide proper recommendations. The purposes of this research are (1) to evaluate the implementation ofmanagement audit function of human resource and (2) to analyze the effectiveness and efficient rates of functionof human resources. The analysis method has been done by using qualitative descriptive and the data collectiontechnique is carried out by conducting interview, questionnaire, and direct observation at PT Prima PersadaNusantara. The result of this research shows that PT Prima Persada Nusantara does not have human resourceplanning which has been documented properly and in the last steps of the selection the personnel department isnot the only department which has its authority to pass the candidate of employee but each division manager alsohas. The implication of the implementation of management audit has been expected that it can assess theeffectiveness of the function of human resources, to assess whether the activity of human resources has beenrunning economically, effectively, efficiency and it can become the supporting instrument to formulateappropriate remedial steps for the company.Keywords: Management Audit, the function of Human Resource, Effectiveness and Efficiency